The effect of electromagnetic treatment on decrease of pathogens in seeds and plants of - I. P. Talanov; L. Z. Karimova; P. I. Talanov (Зерновое хозяйство России, 2018)
The best control of phyto pathogens on winter rye seeds occurred during combined treatment of seeds with disinfectants and electromagnetic effect for 30 minutes. The largest control over dissemination and development of root rots takes place during combined use of ‘KVCh (30min)+Vial TT, VSK-0.5 l/t’, the excess over the control was 2.1 and 2.5 times and 2.2 and 2.5 times respectively to the fertilizing statuses. The maximum decrease of infection with lead diseases was achieved with a combined use of a disinfectant and KVCh (30min). The maximum productivity of grain (3.84 t/ha) was obtained after fertilizing of calculated doses of mineral fertilizers and 4.0 t/ha after a combined use of ‘KVCh (30min)+Vial TT, VSK-0.5 l/t’; the productivity increase after seed treatment was 0.49 t/ha.